Apical CLC‐2 in retinal pigment epithelium is crucial for survival of the outer retina. Issue 7 (4th June 2021) - Hanke‐Gogokhia, Christin; Lehmann, Guillermo L.; Benedicto, Ignacio; de la Fuente‐Ortega, Erwin; Arshavsky, Vadim Y.; Schreiner, Ryan; Rodriguez‐Boulan, Enrique
Abstract: Knockout of the chloride channel protein 2 (CLC‐2; CLCN2) results in fast progressing blindness in mice. Retinal Pigment Epithelium (RPE) and photoreceptors undergo, in parallel, rapid, and profound morphological changes and degeneration. Immunohistochemistry and electron microscopy of the outer retina and electroretinography of the CLC‐2 KO mouse demonstrated normal morphology at postnatal day 2, followed by drastic changes in RPE and photoreceptor morphology and loss of vision during the first postnatal month. To investigate whether the RPE or the photoreceptors are the primary cause of the degeneration, we injected lentiviruses carrying HA‐tagged CLC‐2 with an RPE‐specific promotor in the subretinal space of CLC‐2‐KO mice at the time of eye opening. As expected, CLC‐2‐HA was expressed exclusively in RPE; strikingly, this procedure rescued the degeneration of both RPE and photoreceptors. Light response in transduced eyes was also recovered. Only a fraction of RPE was transduced with the lentivirus; however, the entire RPE monolayer appears healthy, even the RPE cells not expressing the CLC‐2‐HA. Surprisingly, in contrast with previous physiological observations that postulate that CLC‐2 has a basolateral localization in RPE, our immunofluorescence experiments demonstrated CLC‐2 has an apical distribution, facing the subretinal space and the photoreceptor outer segments. Our findings suggest that CLC‐2 does not play the postulated role in fluid transport at the basolateral membrane. Rather, they suggest that CLC‐2 performs a critical homeostatic role in the subretinal compartment involving a chloride regulatory mechanism that is critical for the survival of both RPE and photoreceptors.